2004
DOI: 10.1080/15459620490432114
|View full text |Cite
|
Sign up to set email alerts
|

Physical Work Limits for Toronto Firefighters in Warm Environments

Abstract: This study examined the relationship between time to reach critical end points (tolerance time [TT] and metabolic rate for three different environmental temperatures (25 degrees C, 30 degrees C, and 35 degrees C, 50% relative humidity), while wearing firefighting protective clothing (FPC) and self-contained breathing apparatus (SCBA). Thirty-seven Toronto firefighters (33 male and 4 female) were divided into four work groups defined as Heavy (H, n = 9), Moderate (M, n = 9), Light (L, n = 10), and Very Light (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 28 publications
1
61
1
2
Order By: Relevance
“…The added burden of wearing protective clothing, which increases thermal strain by placing a greater metabolic cost and lowers heat loss opportunities for the individual, is likely to compound the problems of hypohydration. Further, reduced heat dissipation and sweat evaporation from the limited vapour permeability, continually increases body heat storage (Selkirk and McLellan 2004). This will be further affected by greater respiratory demands (Bygrave et al 2004) from the SCBA, causing greater rates of oxygen consumption and metabolic heat production, thus increasing the rate of body temperature and the risks for heat related illnesses.…”
Section: Hydrationmentioning
confidence: 99%
“…The added burden of wearing protective clothing, which increases thermal strain by placing a greater metabolic cost and lowers heat loss opportunities for the individual, is likely to compound the problems of hypohydration. Further, reduced heat dissipation and sweat evaporation from the limited vapour permeability, continually increases body heat storage (Selkirk and McLellan 2004). This will be further affected by greater respiratory demands (Bygrave et al 2004) from the SCBA, causing greater rates of oxygen consumption and metabolic heat production, thus increasing the rate of body temperature and the risks for heat related illnesses.…”
Section: Hydrationmentioning
confidence: 99%
“…Furthermore, these physiology-focused studies typically employ temperatures that are relatively constant, which is different than the continuously varying temperatures typically encountered on the training ground ( Figure 9). As Selkirk and McLellan [23] have shown, physiological responses to activities in PPE are affected by the temperature of the environment, so these differences should be considered in future iterations of firefighter physiological studies where possible. Finally, the effect of heat flux on firefighter physiological responses has not been studied to the same level of detail as exposure to high ambient air temperature environments.…”
Section: Comparison Of Structure Temperatures To Immediate Environmentmentioning
confidence: 99%
“…Some studies have utilized training drills with environmental temperatures less than 100°C in a live-fire burn structure to simulate fire ground activities [18][19][20][21][22]. More commonly, research groups have used a treadmill protocol in a temperature-controlled ( 25°C to 50°C) room [23][24][25][26][27][28]. While Selkirk and McLellan have shown that the physiological responses to activity in fire fighting PPE is affected by the ambient temperature of the testing environment, there are limited data available upon which to base the representative thermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…하지만 개선된 소방방화복의 다층화된 구조는 무게를 증가 시켰으며 수증기의 배출이 어려워지고 열교환율이 감소하여 체온조절을 어렵게 만들었다. 이는 직무 수행시 소방공무원을 더욱 힘들게 하였으며, 다수의 연구자들은 소방방화복을 입고 작업시 에너지소모량을 증가시킨다고 보고하고 있다 (2,3) . (8) , NISOH (9) , ACGIH (10) (12) .…”
Section: 서 론unclassified